Víme, co si o nás Američané myslí? - Krblichová, Jana (Lidé města, 2000)
The author presents the results of the question How do you think Americans see Czechs and Czech society? The question was asked within a broadly conceived survey focusing on the view held by Czech students about U. S. nationals. It was conducted at three Prague secondary schools between 1998 and 1999. The questionnaire included 28 questions. The asked question How do you think Americans see Czechs and Czech society? reflected not only the ideas of Czech students, but also showed what students think of their own society. The idea about the Americans' view had four alternatives. There was an antipode of a belief in negative and positive views of Americans about Czech society. A bigger group said that Americans regard the Czech Republic as an underdeveloped, backward and primitive country. But there were also views saying that Americans are absolutely tolerant as they assess individuals, not nations or countries. Basically, there was the prevailing view that the Czech Republic is a country unknown for Americans, and Czechs a nation virtually non-existent for them.